PRIMARY PROPHYLAXIS IN PREVENTING 1ST BLEED IN OESOPHAGEAL VARICIES: Axis in Preventing Bleed in Oesophogeal Varicies - Iqbal, Brig Muhammad; Utra, Khursheed; Qadir, Adnan; Khattak, Farooq; Khattak, Javaid Iqbal (Pakistan Armed Forces Medical Journal, 2010)
Objective: To study the efficacy of oesophageal band ligation versus use of β-blockers for primary prophylaxis of 1st variceal bleed in portal hypertension Study Design: Randomized controlled trial Place and duration of study: At department of Medicine and Gastroenterology, Combined Military hospital Rawalpindi, during June 2006 to June 2007 Patients and Methods: Sixty eight patients with portal hypertension were included in the study after screening endoscopy. All the patients were divided in two groups, A and B. Group A patients underwent oesophageal band ligation and patients in group B were given β-blockers for primary prophylaxis. Each group contained equal number of 34 patients to start with but in the very first week, 6 patients in group B could not tolerate β blockers. They were switched to group A treatment. These patients were followed up for next one year Results: Group A patients who underwent band ligation had significantly reduced incidence of 1st variceal bleed(p value=0.020) as compared to group B who received β-blockers. As far as mortality is concerned there was no significant difference (p=0.067) was noted between the two groups. Conclusion: The oesophageal band ligation is superior to β -blockers in preventing 1st oesophageal variceal bleed but no difference in mortality was noted whichever prophylaxis was used in this study.